Aprepitant Inhibits JNK and p38/MAPK to Attenuate Inflammation and Suppresses Inflammatory Pain - Yang, Yang; Zhou, Wei; Xu, Xiuqi; Ge, Xianxiu; Wang, Fei; Zhang, Guang-Qin; Miao, Lin; Deng, Xueting (Frontiers in Pharmacology, 2022)
Substance P contributes to the pathogenesis of pain by acting on NK-1R, specialized sensory neurons that detect noxious stimuli. Aprepitant, an antagonist of NK-1R, is widely used to treat chemotherapy-induced nausea and vomiting. In this study, we used LPS-stimulated BV-2 microglia cell line and animal models of inflammatory pain to explore the analgesic effect of aprepitant on inflammatory pain and its underlying mechanism. The excitability of DRG neurons were measured using whole-cell patch-clamp recordings. The behavioral tests were measured and the morphological changes on inflamed paw sections were determined by HE staining. Changes in the expressions of cytokine were measured by using real-time quantitative PCR analysis and ELISA method. Immunofluorescence and western blotting were used to detect the microglia activation and MAPK. Aprepitant treatment significantly inhibited the excitability of DRG neurons. The pain behavior and the paw tissues inflammatory damage were significantly relived after the administration of aprepitant compared to formalin group. Aprepitant significantly suppressed the activation of microglia, phosphorylation of JNK and p38 MAPK, as well as the mRNA and protein expressions of MCP-1, TNF-α, IL-6, and IL-1β, in vivo and in vitro. The LPS-induced over-translocation into nucleus of NF-κBp65 was down-regulated following aprepitant treatment in BV-2 cells. The present study suggests that aprepitant attenuates inflammatory pain in mice via suppressing the phosphorylation of JNK and p38, and inhibiting the NF-κB signaling pathway.